Assessment of the Bioactive Potential of Cheese Whey Protein Hydrolysates Using Immobilized Alcalase - da Cruz, Clariana Zanutto Paulino [UNESP]; de Mendonça, Ricardo José; Guimaraes, Luís Henrique Souza; dos Santos Ramos, Matheus Aparecido [UNESP]; Garrido, Saulo Santesso [UNESP]; de Paula, Ariela Veloso [UNESP]; Monti, Rubens [UNESP]; Massolini, Gabriella (Springer Nature, 2020)
The hydrolysis of bovine cheese whey (BCW) proteins was performed by the Alcalase immobilized on the support glyoxyl-corn-cob-powder (AGCCP). The whey protein hydrolysates (WPH) obtained with AGCPP were fractionated by RP-HPLC according to the hydrophilicity of the peptides (F1, hydrophilic; F2, intermediate hydrophilicity; and F3, hydrophobic). The fractions were analyzed by MALDI-TOF, and molecular weight peptides (< 1500 m/z) were identified. Total WPH obtained by AGCCP presented high capacity reduction of the ABTS radical (57.82%) and high chelating activity of iron II (76.2%). The obtained peptides showed high antimicrobial activity (87.75–100%) against the species Escherichia coli (ATCC 43895) and Listeria monocytogenes (ATCC 7644). Only F2 was effective against the Candida albicans strain ATCC 18804 tested (MIC = 10 mg/mL). The results of this study show that the hydrolysis of BCW proteins using the AGCCP derivative represents a very interesting and viable way for obtention of bioactive peptides from cheese whey.
Keywords: Alcalase; Bioactive peptides; Enzyme immobilization; Whey proteins